Madrasah Digital Reputation Management Model: The Synergy of Transformational Leadership and Digital Branding Strategies - Muhammad Nagib; Akhmad Fauzi Hamzah (Islamic Religious Education Master Program Universitas Islam Internasional Darullughah Wadda'wah, 2026)
ABSTRACT The rapid digital transformation of the modern education sector heavily demands that Islamic educational institutions, specifically madrasahs, adapt their public communication strategies to maintain global competitiveness. This study aims to comprehensively analyze the strategic role of madrasah principals in enhancing institutional reputation through social media, utilizing the combined perspectives of transformational leadership and digital reputation management. Employing a qualitative descriptive-analytical approach, primary data were meticulously collected through in-depth interviews with principals and public relations teams, netnographic digital observation of official social media platforms, and documentation analysis. The findings reveal that madrasah principals effectively act as digital strategic leaders who formulate ethical, Islamic-based digital branding policies. Furthermore, these policies are executed through highly consistent educational content management, achievement-based storytelling, and professional visual branding. Consequently, this strategic execution fosters an authentic two-way dialogic communication culture, significantly increasing public engagement, stakeholder trust, and brand equity. The study successfully synthesizes these interrelated elements into a novel conceptual model of Digital Reputation Management. This model demonstrates a virtuous circle where active digital engagement directly elevates institutional competitiveness. Ultimately, this research implies that highly effective madrasah leadership requires integrating technological vision with spiritual values to sustainably navigate the digital era.